Rancang Bangun Sistem Informasi Berbasis Web sebagai Media Informasi dan Portal Pembelajaran pada SMP Setia Negara Depok - Farhan Baihaqi; Muhamad Al Happsi; Erico Dwi Antoro Perez; Maulana Ardhiansyah (CV. Shofanah Media Berkah, 2026)
This study aims to design and build a web-based school information system as an information medium and learning portal at SMP Setia Negara Depok. The main problems identified were the limited distribution of school information and the absence of an integrated digital learning facility for teachers and students. Data were collected through observation, interviews, and literature study, while the software development method used was Prototype. The development stages included needs analysis, prototype design, prototype evaluation with the school, system development, testing, implementation, and maintenance. The system consists of a public school information website and a learning portal with admin, teacher, and student access rights. The main features include school profiles, teacher data, facilities, achievements, education fees, schedules, learning materials, assignments, grades, QR Code attendance, announcements, and account management. Testing was conducted using Black Box Testing on website features, admin dashboard, teacher dashboard, and student dashboard. The test results showed that the tested features worked according to the expected outputs, so the system is feasible as a design for digital information media and learning support at SMP Setia Negara Depok.